Usapang babae gender awareness through theater arts, games and processes. (National Commission on the Role of Filipino Women, 1992)
Theater for grassroots education. Basic workshop for gender awareness. Alternative and supplementary exercises. "This is primarily a manual for gender awareness facilitators who have undergone training in the use of theater games and processes and facilitator's adept in gender issues and theater techniques." It is a workshop book with modules in scheduled sessions.